Philosophy and Opinions of Marcus Garvey - Jacques - Garvey, A. (The Universal Publishing House, 56 West 135th Street, New York City, U. S. A., 1923)
This volume is compiled from the speeches and articles delivered and written by Marcus Garvey from time to time. My purpose for compiling same primarily, was not for publication, but rather to keep as a personal record of the opinions and sayings of my husband during his career as the leader of that portion of the human family known as the Negro Race.
Keywords: Opinions; Philosophy